The synthesis and evaluation of new butadiene derivatives as tubulin polymerization inhibitors. Issue 12 (15th June 2017) - Pang, Yanqing; Yan, Jun; An, Baijiao; Huang, Ling; Li, Xingshu
Graphical abstract: Abstract: A series of new butadiene derivatives was synthesized and evaluated as tubulin polymerization inhibitors for the treatment of cancer. The optimal butadiene derivative, 9a, exhibited IC50 values of 0.056–0.089 μM for five human cancer cell lines. This paper included a mechanistic study of the antiproliferative activity, including a tubulin polymerization assay, an examination of morphological alterations of cancer cells, an analysis of cell cycle arrest and an apoptosis assay.